Disability and Migration Routes: An Explorative Analysis Among Refugees Hosted in Italy - Marco Tofani; Marco Tofani; Maurizio Marceca; Maurizio Marceca; Donatella Valente; Donatella Valente; Giovanni Galeoto; Giovanni Galeoto; Mohamed Ali Ben Zina; Imène Soumaya Salhi; Khadija Elmadmad; Khadija Elmadmad; et al. (International Journal of Public Health)
ObjectiveData on disability in refugees is lacking, hindering effectiveness of humanitarian response. We investigated disability condition in refugees, identifying possible mechanisms that affect their health.MethodsThe Washington Group Short Set – Enhanced was used to identify people at risk experiencing disability. Data on migration routes were collected and the relationship with functioning limitations was explored.Results483 refugees (58.18% males - 41.82% female) were interviewed. 23.8% were found to have a disability, with a higher risk for those who travelled along the central Mediterranean route OR (95% CI) 2.08 (1.33–3.24). Affect domain represented the main weight for disability (28.16%), followed by mobility limitation (8.28%). People who travelled across the central Mediterranean route were found to have a high risk of developing anxiety problems OR (95% CI) 2.19 (1.33–3.6), while people who crossed the Balkan route had a higher risk of mobility limitation OR (95% CI) 3.03 (1.23–7.44).ConclusionThis study provides the first available data on disability among refugees in Italy, revealing a high prevalence of disability and a significant association with migration routes. These findings underscore the urgent need for targeted health and rehabilitation interventions to address the specific vulnerabilities of this population.